Elements of ancient Jewish nationalism - Goodblatt, David M. (Cambridge University Press, 2006)
Theoretical considerations : nationalism and ethnicity in antiquity -- Constructing Jewish nationalism : the role of scripture -- Constructing Jewish nationalism : the Hebrew language -- A kingdom of priests : the priestly component in ancient Jewish nationalism -- Israel nationalism -- Judah nationalism -- Zion nationalism -- Conclusions : Jewish nationalism : what rose and what fell? -- Bibliography